Novel drug candidates targeting Toxoplasma gondii in maternal–fetal interface models - de Oliveira, Rafael Martins; Lima dos Santos, Natália Carine; Almeida, Marcos Paulo Oliveira; Lima Júnior, Joed Pires De; Souza, Guilherme De; Barbosa, Matheus Carvalho; Faria, Guilherme Vieira; Paschoalino, Marina; Alves, Rosiane Nascimento; Gomes, Angelica Oliveira; Reimão, Juliana Quero; Barbosa, Bellisa Freitas; et al. (Frontiers in Pharmacology, 2025)
IntroductionToxoplasmosis is a disease caused by the protozoan Toxoplasma gondii. Infection during pregnancy can lead to congenital toxoplasmosis, which is associated with severe outcomes such as fetal abnormalities, stillbirths, and miscarriage. Current treatment options for congenital toxoplasmosis have several limitations, including low efficacy in the chronic phase of the disease and concerns about potential fetal toxicity, such as bone marrow suppression and teratogenic effects. Therefore, there is an urgent need for more effective and safer therapeutic alternatives. The Medicines for Malaria Venture (MMV) offers a collection of bioactive compounds with antiparasitic potential for drug repurposing.MethodsIn this study, we evaluated three MMV Pathogen Box compounds—MMV675968, MMV022478, and MMV021013—for their ability to control T. gondii infection in human trophoblastic cells (BeWo) and third-trimester placental villous explants. We assessed compound toxicity, effects on the parasite’s lytic cycle (including adhesion and infection), alterations in parasite morphology, and the host immune response through cytokine quantification.ResultsNontoxic concentrations of all the three compounds irreversibly inhibited parasite proliferation and interfered with early stages of the lytic cycle, including adhesion and infection. Moreover, treated T. gondii tachyzoites exhibited membrane disruption, cytoplasmic degradation, and organelle disorganization. The cytokine profile indicated that compound treatment promoted an anti-inflammatory immune response, primarily by reducing IL-8 levels. Importantly, these compounds also effectively controlled T. gondii infection in human placental explants without inducing cytotoxicity.ConclusionTaken together, our findings support the potential of MMV675968, MMV022478, and MMV021013 as promising drug candidates for the treatment of congenital toxoplasmosis. MMV021013 stands out as the most promising compound, combining high predicted gastrointestinal (GI) absorption and blood–brain barrier (BBB) permeability, with no predicted mutagenic, tumorigenic, irritant, or reproductive effects.